Role of technology in Supporting Quality Control and Treatment Fidelity in a Family Caregiver Clinical Trial - Farran, Carol J. (2011)
This article describes how a family caregiver lifestyle physical activity clinical trial uses research technology to enhance quality control and treatment fidelity. This trial uses a range of Internet, Blaise® Windows-based software, and Echo Server technologies to support quality control issues such as data collection, data entry and study management advocated by the clinical trials' literature, and to assure treatment fidelity concerning intervention implementation (i.e., design, training, delivery, receipt and enactment) as proposed by the National Institutes of Health Behavior Change Consortium. All research staff are trained to use these technologies. Strengths of this technological approach to support quality control and treatment fidelity include the comprehensive plan, involvement of all staff, and ability to maintain accurate and timely data. Limitations include the up-front time and costs for developing and testing these technological methods, and having support staff readily available to address technological issues if they occur.